Examining the Implications of Political Thuggery on Electoral Process in Nigeria - Hyginus Obinna Ogbonna; Benedict Ibukun Ajayi; Bello Eugene O. (Mediterranean Journal of Social Sciences, 2022)
The paper focuses on examining the implications of Political Thuggery on Electoral Process in Nigeria. Its general objective is to examine the effects of political thuggery or violence on electoral process with inferences from Nigeria; with specific objectives to i). Identify the implications of Political Thuggery to national security, and ii). proffer policy-based recommendations including implementation strategies to curbing the anomalies. The paper achieved its objectives by adopting qualitative descriptive method of analysis; its instruments of data collection included secondary sources --books, newspapers, journals, internet, and observations of the trend of political activities in Nigeria. For Indepth understanding of the discourse, the paper made extrapolations from three (3) relevant notions: the notions of Democratic Culture, Vested Interest, and Legitimation-crisis. In its investigation, relevant finding or outcome was made. The finding revealed that there is a positive correlation between Political Thuggery and Electoral Process --that is, the more political thuggery increases, the more electoral process anomalies increase too. The paper therefore concluded that, political thuggery has negative implications to national security. A few recommendations were proffered: 1. Salaries of political officers should be reduced to make political office less attractive, thus making politics no more a "do or die" affair; inter alia. Received: 11 July 2022 / Accepted: 25 August 2022 / Published: 2 September 2022